2018
DOI: 10.1177/1558944718769382
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Conduit-Assisted Primary Nerve Repair Strength With Varying Suture Size, Number, and Location

Abstract: Conduit-assisted primary digital nerve repairs with 8-0 suture increases the maximum load to failure compared with repairs with 9-0 suture, as does increasing the overall number of sutures. Using 9-0 suture at the coaptation site with 8-0 suture at the nerve-conduit junction does not jeopardize tensile strength when compared with similar repairs using all 8-0 suture and may decrease inflammation at the repair site while still achieving sufficient tensile strength.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 23 publications
1
10
0
Order By: Relevance
“…Nerve cap grafts were assessed for suture retention strength using the setup shown in Figure 5A. All graft walls ( n = 10) failed with a peak force between 1.145 and 2.97 N with an average peak force of 1.93 ± 0.6 N suggesting that the nerve cap grafts had mechanical properties which were suitable for suture in nerve repair applications 13 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nerve cap grafts were assessed for suture retention strength using the setup shown in Figure 5A. All graft walls ( n = 10) failed with a peak force between 1.145 and 2.97 N with an average peak force of 1.93 ± 0.6 N suggesting that the nerve cap grafts had mechanical properties which were suitable for suture in nerve repair applications 13 …”
Section: Resultsmentioning
confidence: 99%
“…All graft walls (n = 10) failed with a peak force between 1.145 and 2.97 N with an average peak force of 1.93 ± 0.6 N suggesting that the nerve cap grafts had mechanical properties which were suitable for suture in nerve repair applications. 13 The nerve cap graft grafts were successfully attached to both the proximal and distal ends of the sciatic nerve at the time of implantation, with the proximal end of the nerve inserted into the nerve cap graft socket. The diameter of the graft was observed to be greater than that of the peripheral nerve trunk, and the trunk fit well within the socket of the graft.…”
Section: Mechanical Propertiessuture Retentionmentioning
confidence: 99%
“…Hyperextension of 30° may be a more physiologic amount of hyperextension experienced in normal activities of daily living. Multiple studies have looked at nerve repairs using various repair techniques and have reported ultimate failure between 1 and 2 N. 7,9-12 Hyperextension of 30° or less would then not produce failure of these repairs. However, the maximum tension of 0.64 N approaches or exceeds the failure strength of “glue”-only repair constructs.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4] When the number of sutures decreases, the strength of the nerve repair line decreases, 5 and fringing and gaps occur at both ends, exerting negative effects on the healing process. 6 For this reason, each additional suture has its benefits and disadvantages, and this situation puts the procedure into a dilemma.…”
mentioning
confidence: 99%